A Systematic Literature Review on Micro, Small, and Medium Enterprises (MSMEs) Performance: National and International Evidence - Asmar, Asmar; Adriansyah, Adriansyah; Anas, Agung Muliaman (PT Mattawang Mediatama Solution, 2025)
This study investigates the performance of Micro, Small, and Medium Enterprises (MSMEs) by synthesizing evidence from recent empirical studies through a systematic literature review approach. The research analyzes thirty-three peer-reviewed journal articles published between 2020 and 2025 that explicitly discuss MSME performance from multidimensional perspectives. The data collection process followed established systematic review protocols, including identification, screening, eligibility, and inclusion of relevant literature. The methodology employed thematic content analysis to classify findings into four major categories: performance measurement, internal determinants, external support, and international comparisons. The results reveal that MSME performance is not only measured by financial indicators such as profit, revenue, and cash flow but also by non-financial aspects including innovation, customer satisfaction, and sustainability criteria. The analysis shows that innovation, entrepreneurial orientation, financial literacy, and human resource capacity are the most influential internal factors, while government policies, financial institutions, market access, and infrastructure represent crucial external enablers. The findings further indicate that digitalization and technology adoption play a pivotal role in strengthening MSME competitiveness and resilience, particularly during economic crises and the COVID-19 pandemic. Finally, the review highlights significant differences between developing and developed countries, where MSMEs in emerging economies face more structural challenges yet often experience greater marginal benefits from digital transformation.